Exceptions to the Right to Be Forgotten in Relation to Press Freedom in the Digital Era - Theon Charles; Kiki Kristanto; Rizki Setyowibowo Sangalang (Journal of Law, Politic and Humanities, 2025)
The rapid development of technology has significantly transformed the dissemination and accessibility of information in Indonesia. With 77% of the population being internet users in 2023, issues surrounding personal data protection and freedom of the press are becoming increasingly critical. The "Right to be Forgotten" (RTBF), inspired by the European Union's GDPR framework, has been incorporated into Indonesia's Personal Data Protection Act No. 27 of 2022. This legislation grants individuals the right to erase personal data under certain conditions. However, this right faces challenges when it intersects with press freedom, a cornerstone of democracy. The Indonesian law does not explicitly address the exemption of RTBF in the context of freedom of expression and public interest reporting, unlike the GDPR. This gap potentially poses a threat to journalistic activities, especially in reporting sensitive issues like legal proceedings or public figures' misconduct. This study employs a legal research method with statute, conceptual, and comparative approaches to analyze this intersection. The findings highlight the need for balanced regulations that protect personal privacy without undermining press freedom. As such, considering technological advancements and societal needs, is essential for ensuring the coexistence of these fundamental rights.